Simpole Owl In Arabic And Persian Culture - عبد الرضا, سیف; ،حمیرا, زمردی; ،عنود, جمعه (Al-Adab Journal, 2018)
Generally, animals have a symbolic role in the literature of different ethnic groups, and in some ways they express the views and customs of different cultures. Perhaps the animal in the literature of some people is a symbol of peace and friendship and, in other people's beliefs, a symbol of hostility . One of the animals with the greatest contradictions is the owl. An animal that, despite its many denunciations in some cultures, has its own position, albeit a negative one. There,the owl is given different attributes. What the place of dispute and discussion among the researchers of the field of literature is that traits such as naked and neglected facts are the origins of Persian or Arabic culture or are they interacting with each other due to the proximity of the two cultures?In this research, the author attempts to examine the role and position of the owl in the Zoroastrian texts of the Pahlavi and Avestan, as well as in Arabic poetry and beliefs before Islam. The study of the presence of the owl symbol in Persian and Arabic stories and the differences and similarities between them in Arabic and Persian peoples until the fall of Baghdad will be among the other goals of this study. For this purpose, two of the masterpieces of Persian literature (Panchatantra and a border guard) and three works of prominent Arabic (Alsadh and Albaghm, Kashf al-Asrar fi Altyvr sentence and Alaz·har and resale Alsahl and Alshahj) were selected.